2021
DOI: 10.3390/en14144083
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Characterization of the Pellet Obtained from Hazelnut and Olive Tree Pruning

Abstract: Biomass occupies a very important place among renewable energy sources, and the residual biomass recovery chain represents a sector of fundamental importance. Our work focused on the production of pellets by pruning residues from two of the most important woody crops in Italy: hazelnut and olive groves. We found a higher value of bulk density for the hazelnut pellet (581.30 kg m−3 vs. 562.38 kg m−3) and a higher value of length for the olive pellet (16.66 mm vs. 10.47 mm). The percentages of durability were ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…In the last few years, hazelnut wastes have been studied to derive value from the production of medicinal mushrooms, biopellet production, etc. 5 , 6 . Composting is another way to add value to them.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, hazelnut wastes have been studied to derive value from the production of medicinal mushrooms, biopellet production, etc. 5 , 6 . Composting is another way to add value to them.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being an important renewable energy resource, whether derived from dedicated energy crops or not, it is widely recognised that woody biomass is characterised by low energy density, high moisture content, heterogeneous geographical distribution and high transport costs that limit its wider use as an energy source [11][12][13]. These drawbacks can be overcome by applying a process of densification, or rather pelletisation, to the source woody material, which optimises the use of this solid biofuel as an energy feedstock [14][15][16][17][18], improving storage and facilitating the logistics and supply of power plants and small individual boiler rooms [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The pellet, therefore, comes in a cylindrical form with a diameter of 6-8 mm and an average length of 10-12 mm, which is easy to package and use [24,25]. The starting woody material can be represented by residues from wood processing (sawdust), by wood chips obtained from residues of treetops and forest branches, or even materials derived from the use of dedicated energy systems (SRC) or by residues of agroforestry pruning [9,18,[26][27][28][29]. Naturally, the transition from raw wood material to pellets involves a production process consisting of several steps that necessarily increases the cost of the finished product.…”
Section: Introductionmentioning
confidence: 99%
“…An example is an Italian study that assessed the energy performance of pellets made from hazelnuts and olives obtained by pruning on local farms. The research showed a slight deterioration in the quality of the produced pellets, and further research was proposed to determine the appropriate ratio of the given materials with clean sawdust (Acampora et al 2021). It is also possible to press waste shells into larger forms, which was effectively demonstrated in one Indonesian study using local cashew nut shells waste to make briquettes (Ifa et al 2020).…”
Section: Introductionmentioning
confidence: 99%